2008
DOI: 10.1088/0022-3727/41/2/025205
|View full text |Cite
|
Sign up to set email alerts
|

Coupled gas and ion transport in quadrupole interfaces

Abstract: The transport of free ions through highly under-expanded jet flows of neutral gases and in the presence of applied electric fields is investigated by continuum-based (fluid) numerical simulations. In particular, numerical results are described which are relevant to ion flows occurring in quadrupole interfaces of mass spectrometer systems. A five-moment mathematical model and parallel multi-block numerical solution procedure are developed for predicting the ion transport. The model incorporates the effects of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…One plausible explanation for doubly protonated bombesin requiring higher pressure to reach a maximum intensity is that its kinetic energy was significantly higher than that of caffeine, both due to its higher mass and its being doubly charged. Immediately after the ions are transferred into the vacuum, the velocities of ions of small and large mass are expected to be similar,55 which makes the kinetic energies of the high‐mass ions higher (until thermal equilibrium, a pressure‐dependent process, is established). Additionally, in comparison with caffeine, doubly charged bombesin ions gain more kinetic energy along the ion optical axis by the DC electric field (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…One plausible explanation for doubly protonated bombesin requiring higher pressure to reach a maximum intensity is that its kinetic energy was significantly higher than that of caffeine, both due to its higher mass and its being doubly charged. Immediately after the ions are transferred into the vacuum, the velocities of ions of small and large mass are expected to be similar,55 which makes the kinetic energies of the high‐mass ions higher (until thermal equilibrium, a pressure‐dependent process, is established). Additionally, in comparison with caffeine, doubly charged bombesin ions gain more kinetic energy along the ion optical axis by the DC electric field (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Physical phenomena involved in electrosprays (such as production of charges and transport) can be complex 6, 23, 24. In the second part of the paper, the droplet formation in the capillary needle prior to the application of an electric field is also investigated.…”
Section: Resultsmentioning
confidence: 99%
“…However, focusing ions at atmospheric pressure toward a vacuum aperture using only dc fields is counteracted by Gauss’s law and the subsequent divergence of ion trajectories on the vacuum side of a simple aperture . It has been reported that the vacuum drag force due to the pressure gradient dominates over the effects of electric fields in the vicinity of a sampling capillary inlet. , In other words, optimizing the geometry in the region between the ablation site and the sampling inlet is crucial for sampling ions efficiently. In both scanning AP MALDI-MS and AP LDI-MS, the transport of ions through the metal capillary of a linear trap quadrupole (LTQ) mass spectrometer is limited by space-charge effects, which is of course not an issue for neutral molecules.…”
Section: Resultsmentioning
confidence: 99%